Measurements of different Silicon Car bide Transistors and their Varying Con duction Losses when used in Three-Phase Inverters - Kourjian, George (My University, 2025)
Abstract In this bachelor thesis, the spread of RDS(on) is measured and quantified for five SiC MOSFET samples from each of three different manufacturers. The resulting spread in on-state resistance was then applied theoretically to a three-phase inverter model in order to calculate the corresponding conduction loss variation. The conduction loss was determined using an algebraic equation based on the MOSFET parameters, specifically the on-state resistance and drain-source current. Finally, the measured maximum and minimum conduction losses were compared to typical values from each manufacturer’s datasheet, with the results expressed as relative percentage deviations, scaled to represent the total conduction loss across all six MOSFETs in a three-phase inverter. The results show that the spread of RDS(on) was significant within each manufacturer, with standard deviations ranging from 3.1 mΩ for Onsemi to 6.4 mΩ for Infineon. This spread was calculated for two gate voltages. When the measured RDS(on) values were used to calculate conduction losses, the variation resulted in substantial differences in total inverter loss. For Infineon, the conduction loss ranged from –34.8% to +42.4% relative to the typical datasheet-based value. STM exhibited the largest deviation, reaching up to +52.2%. In contrast, Onsemi showed a more modest variation, with losses between –7.7% and +26.5%. These findings highlight the importance of accounting for RDS(on) spread when estimating conduction losses in practical three-phase inverter designs.
Keywords: Keywords: Power electronics, SiC, MOSFET, Conduction losses, Python, Threephase inverter